Customer Satisfaction Research as Basis Data for New Product Development, Case Study : Insan Gemilang Indonesia - Syah, Muhammad Mahbub; Chaldun, Evy Rachmawati (Journal of Innovation, Business and Entrepreneurship, 2019)
Abstract. The world nowadays has a prominent idea to transform, while education is one of the crucial aspects that should put give attention to everyone. Education as a right and education as an obligation may reflect the status quo. Provision of gaining quality of education can’t be reduced as the role of Government only. Here, startups from private sector could provide the best education in so many ways. Insan Gemilang Indonesia as one of the biggest education service in Science Olympiad market has created more accessible and inclusive service to school who really want to achieve and increase quality of Science Olympiad training. Researcher used an exploratory research design by qualitative method with in-depth interview with 11 stakeholders to examine an underlying factor to meet an expectations of customer satisfaction and basis data improvement. The research question focused on the rate of customer satisfaction and their preference to IGI service. The research finding from customer’s perspectives used as an evaluation and data for IGI’s continuous improvement.Keywords: Customer satisfaction, Insan Gemilang Indonesia, Education service, Product development.